The attacks of September 11, 2001 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic, 2012)
When Lucas decides to skip school because he wants to discuss football with a firefighter friend of his father, he finds himself caught up in the terrorist attacks on New York City.
Keywords: September 11 Terrorist Attacks, 2001 -- Juvenile fiction; Terrorism -- New York (State) -- New York -- Juvenile fiction; Adventure stories; Historical fiction